Asarum ampulliflorum (Aristolochiaceae), a new species from Taiwan - Lu, Chang-Tse; Wang, Jenn-Che (Phytotaxa, 2014)
Asarum ampulliflorum Lu & Wang, sp. nov. (Aristolochiaceae), collected from Taiwan, is described and illustrated here. Asarum ampulliflorum is similar to A. asaroides (Morr. & Decne.) F. Maekawa in appearance but can be differentiated from the latter by leaf length equal to width (vs. length longer or shorter than width), perianth tube smaller (8.7–11.7 mm × 13.8–18.1 mm vs. 20.0–25.0 mm × 25.0–30.0 mm) and more compressed (ratio of the perianth tube length to the diam. at the widest points of tube 0.62−0.66 vs. 0.80−0.83), and limb lobe nearly as long as perianth tube (vs. shorter than perianth tube). We have compared the species with similar species in Taiwan and east Asia and have provided an artificial taxonomic key for A. ampulliflorum and related species.